(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2024)
Environmental migrants have gained global relevance because of climate change, which results in greater occurrences of disasters and forces people to move in search of safer living conditions. On the international scene, there are many instruments that deal with the topic, with the reference study object of this article being the Sendai Framework for Disaster Risk Reduction 2015-2030. In this context, the following research problem is presented: how can the Sendai Framework contribute to the legal systems of Brazil and Portugal in relation to dealing with environmental migrants, analyzing how each country recognizes, protects, and supports these individuals? The general objective of this study is to verify how the definition of environmental migration occurs in both countries, in terms of inclusion in the legal system. The specific objectives are: (i) to study the institutes of refuge, asylum, and subsidiary protection, in addition to verifying the correct legal framework to include these groups and identify them within the theme of the Sendai Framework; and (ii) demonstrate the importance of this type of forced displacement, given that the number of climate catastrophes is growing, but is sometimes forgotten by the law. The methods used were basically legal-dogmatic, for the interpretation of the norms relating to the matter and the correct definition of the institutes and analytical, to bring together all the lessons obtained to establish a scientific result in which the proposed objectives are achieved. Finally, it will be demonstrated that the relevant legislation does not provide a satisfactory definition, nor is it linked to the Sendai international framework. However, there is a slow but progressive evolution of these rights, as an example of a historic UN decision in 2020, which sets a precedent for the protection and correct classification of these individuals.